Landholding as a lifeline: The impact of the Rohingya Crisis on farmers in Teknaf and Ukhia - Ahmed, Tasfia (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Social Science in Anthropology, 2023.